HUKUM WARIS DAN KEBUTUHAN BISNIS DALAM WARIS - Nisa Permata Basti; Sanggup L Agustian; Sekar Wiji Rahayu (Jurnal Aktual Justice, 2020)
There are many branches of law related to business law, including Corporate Law, Insurance Law, Banking Law, Inheritance Law, Commercial Law, and so on. The three systems of inheritance law have different perspectives in determining who is the heir, as well as other matters concerning inheritance. This will be explained in the next chapter. The issue of inheritance law always has its own challenges in every case. Starting from the ones that are easy to handle to cases that cause minor wars between families, sometimes even lawyers seek profit from this inheritance law case.